Evaluation of the Performance of Injection Wells in EX Structure - Zona Nuansa Antariksa; Sonny Irawan; Dyah Rini Ratnaningsih; Taufan Marhaendrajana; Rini Setiati; Muhammad Taufiq Fathaddin (Penerbitan Universitas Trisakti, 2022)
One of the efforts that can be done to evaluate the performance of water injection in a field is by monitoring the injector wells. Observations can be made by looking at the flow rate and injection pressure at each injector well. The response given by each injection well will be able to represent the injection performance on a field scale. The EX structure is a structure that has been produced for more than 40 years. In addition, water injection has also been applied for approximately 16 years. There are four injection wells operating in this EX structure with an average injection flow rate of 3000-8000 bwipd per well. Evaluation of injection well performance is carried out by conducting a Hall Plot on each injection well from the start of the injection process to the last data obtained. Based on the evaluation results, it was found that there was plugging in the EA-IIS and EJ-IVS injection wells. Stimulation activity is needed in both wells to restore the well injection capability. Meanwhile, for the EA-IS and EB-IIL injection wells, there are no significant problems in those wells so they can still function properly as injection wells.